Understanding Composite Beam Design Methods Using LRFD - Lorenz, Robert F. (Engineering Journal, 1988)
A recommended source of information for an understanding of Load and Resistance Factor Design concepts is through the composite design sections of the LRFD Specification and LRFD Manual. Specifically, the structural engineer designing a shear-connected composite beam has a new tool in the Composite Beam Selection Tables published in Part 4 of the LRFD Manual. These tables allow the designer much more flexibility in the alternative selection process that leads to better reliability and design economy. To properly exploit these options, however, an understanding of the fundamental composite strength limit theory and the model from which the design tables were created is needed. A particularly attractive benefit is that preliminary design manipulation can proceed with no required information regarding the strength properties of the concrete. When discrete cost parameters of the variable material requirements are known, cost optimization is also feasible.